Cancer incidence among physicians occupationally exposed to ionizing radiation in Finland - Jartti, Pirkko; Pukkala, Eero; Uitti, Jukka; Auvinen, Anssi (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'Occupational radiation exposure was estimated, and the cancer incidence among physicians working with radiation was compared to that of unexposed physicians. ' ' METHODS ': 'A cohort of 1312 physicians was identified from the Finnish occupational radiation exposure registry. Radiation exposure data were obtained from 1970 to 2001 on the basis of individual dosimeters. Never-monitored Finnish physicians (N=15 821) were used as a reference group, identified from census data of Statistics Finland. Incident cancer cases were identified by record linkage with the Finnish Cancer Registry. ' ' RESULTS ': 'The cumulative radiation dose exceeded the recording level (0.3–3.0 mSv during a 3-month period for 1029 radiation-exposed physicians (59.8%). Six percent of the radiologists had received a cumulative dose of 50 mSv or more. Altogether there were 41 cancers observed among the radiation-exposed physicians and 998 cases found in the never-monitored group. Standardized incidence ratios (SIR) for all cancers were comparable with those of the general population among physicians monitored for radiation [SIR 1.0, 95% confidence interval (95% CI) 0.7–1.4] and other physicians (SIR 1.0, 95% CI 1.0–1.1). For specific cancer sites, a slightly elevated risk of female breast cancer was found among monitored physicians when compared with other physicians (rate ratio 1.7, 95% CI 1.0–3.1). No obvious dose-response relationship was found for the overall cancer incidence. ' ' CONCLUSIONS ': 'According to the results from a nationwide cohort, occupational exposure to medical radiation is not a strong risk factor for cancer among physicians. Possible excess risk could not be reliably demonstrated even after the follow-up of a nationwide cohort for up to 30 years.
Keywords: cancer incidence; Finland; ionizing radiation; neoplasm; occupational exposure; physician; radiation effect; radiology; X-ray